IMPORTANCE DES EXPÉRIENCES DANS L’ENSEIGNEMENT ET L’APPRENTISSAGE DU SYSTÈME NERVEUX AU COLLÈGE : ETUDE DE CAS - Houssaini, Wissal Iraqi; Hassouni, Taoufik; Echalfi, Fatima; Ziali, Fatima (European Scientific Journal, ESJ, 2014)
The acquisition of the concept of the nervous system is difficult for learners of 3rd year college. We asked about the possible origins of these difficulties. Our study was conducted with 12 teachers of Life and Earth Sciences and 50 learners of 3rd year college. Our results showed that the lack of conducting experiments in the classroom would be the major cause up to the introduction of false representations in learners. The Information and Communication Technologies in Education, ICT, are a good way of illustration in many disciplines. However, theses technics remain insufficient in the case of teaching and learning the nervous system, an important concept in the program of Life and Earth Sciences.